Penentuan LD50 Penyakit Infeksi Toxoplasma gondii pada Mencit balb/c - Winarto Winarto (MEDIA MEDIKA INDONESIANA, 2009)
LD50 determination in toxoplasma gondii infection in balb/c miceBackground: LD50 is a marker of virulence which is reflects degree of microorganism pathogenicity. LD50 of every pathogens to be used should be determined in order to choose an appropiate infective dose of agent under the study. Toxoplasma gondii RH strain has been maintained in the laboratory by serial passage in mice for several years, in which the biologic and laboratory conditions might has an effect on its virulence. The objective of this study was to determine LD50 of Toxoplasma gondii RH strain used for research in Biotechnology Laboratory Gajah Mada University.Methods: The design of the study was true experiment consisting three goups of 10 female balb/c mice aged 8–10 weeks that were infected with 101, 103 and 106 of Toxoplasma gondii RH strain/mice respectively, and being followed up to day 18. Homogeneity of mice before infection were analyzed by Levence statistic, while the effects of infection was analyzed by Anova. The number of dead mice in each group were recorded and LD50 was calculated base on proportional distance.Results: There was no weight difference between groups of mice before infection. The weight increased up to day 6 in group I and II, while group III after day 3 there was weight decrease. LD50 of Toxoplasma gondii was 1.39x103 which belonged to genotype II of pathogenicity classification.Conclusions: LD50 of Toxoplasma gondii was 1.39x103 which is lower than the original RH strain, and belonged to group II of genotype, which is often reported as the major cause of human and animal infections.Keywords: LD50, Toxoplasma gondii, balb/c mice, infection. ABSTRAKLatar Belakang: Toxoplasma gondii di laboratorium dipelihara dengan cara pasase dari satu mencit ke mencit berikutnya, yang mungkin berpengaruh terhadap virulensinya. LD50 adalah ukuran virulensi suatu mikroorganisme penyebab infeksi, yang harus diketahui apabila akan melakukan penelitian tentang fenomena infeksi pada binatang coba. Tujuan penelitian ini untuk menentukan besar LD50 Toxoplasma gondii strain RH yang disimpan dan digunakan untuk penelitian di Laboratorium Bioteknologi UGM yang belum pernah ditentukan nilai LD50nya.Metode: Disain penelitian adalah eksperimental murni. Tiga kelompok mencit balb/c usia 6–8 minggu masing-masing kelompok terdiri dari 10 mencit, diinfeksi Toxoplasma gondii strain RH secara berturut-turut tiap kelompok diinfeksi dengan 101, 103 dan 106 toksoplasma/mencit, yang diamati sampai hari ke-18. Sebelum perlakuan ketiga kelompok dilakukan tes homogenitas berat badan mencit dengan statistik Levene. Efek infeksi toksoplasma dianalisis dengan Anova, sedangkan LD50 dihitung berdasarkan jarak proporsi.Hasil: Sebelum diinfeksi Toxoplasma gondii, tidak terdapat perbedaan berat badan mencit pada 3 kelompok. Setelah diinfeksi toksoplasma sampai hari ke-6, berat badan mencit pada kelompok I dan II naik, sedangkan kelompok III pada hari ke-1 sampai hari ke-3 beratnya naik, kemudian setelah hari ke-3 beratnya turun. LD50 Toxoplasma gondii strain RH di PAU Bioteknologi UGM didapatkan sebesar 1,39x103 yang sesuai dengan genotipe II.Simpulan: LD50 Toxoplasma gondii sebesar 1,39x103 lebih rendah dari strain RH yang sebenarnya dan termasuk genotipe II yaitu yang paling sering dilaporkan sebagai penyebab infeksi pada manusia dan binatang.